Formulation and Physicochemical Characterization of Herbal Facial Wash Containing Moringa oleifera and Solanum lycopersicum Extracts - Novaliana Devianti Sagita; Meylani Sutoro; Syifa Salsabilla; Reza Pratama (Jurnal Jamu Indonesia, 2026)
Cleansing products based on plant extracts require acceptable physicochemical properties and retained antioxidant activity. This study formulated a herbal facial wash containing Moringa oleifera leaf extract and Solanum lycopersicum fruit extract and evaluated its physicochemical characteristics and antioxidant activity. Three formulas were prepared with different excipient compositions and assessed for organoleptic properties, pH, viscosity, foaming ability, free alkali content, phytochemical profile, TLC pattern, and DPPH radical-scavenging activity. Phytochemical screening detected flavonoids, tannins, saponins, alkaloids, quinones, and triterpenoids. The selected formulation showed chromatographic bands comparable to the extracts, indicating retention of major constituents after formulation. The IC₅₀ values were 30.891 ± 0.40 µg/mL for M. oleifera extract, 50.532 ± 0.92 µg/mL for S. lycopersicum extract, and 46.350 ± 0.08 µg/mL for the selected facial wash. These results indicate that the extracts can be incorporated into a facial wash with measurable antioxidant activity.